Heavy Metal Levels and Risk Assessment of Walnut Genotypes (Juglans regia L.) Grown in Aras Basin of Türkiye - Gülsoy, Ersin; Pehluvan, Mücahit; Şimşek, Uğur; Şanda, Murad Aydın; Şimşek, Miktat (Hohere Bundeslehranstalt und Bundesamt fur Wein- und Obstbau Klosterneuburg, 2024)
Walnuts are among of the most popular nuts worldwide due to their health-promoting compounds, and their consumption is on the rise. This increase in walnut consumption may lead to an increase in the intake of heavy metals in the body. In this study, the levels of the heavy metals Cr, Ni, Pb and Cd were determined in a total of twenty walnut genotypes grown in four different locations in the Aras Basin, and the distribution of these heavy metals according to location was analyzed. While highly significant differences (P<0.001) were found among the walnut genotypes in terms of heavy metal contents, the distribution of these metals among the sites showed differences (P≤0.05). The average amounts of Cr, Ni, Cd and Pb in the walnuts were 476.00 µg kg-1, 202.83 µg kg-1, 2.06 µg kg-1 and 30.64 µg kg-1, respectively. All heavy metals analyzed according to location showed the highest values in Tuzluca. As a result, since the hazard quotient (HQ) which derived from the daily intake rate (DIR) of each trace element analyzed was less than 1 (HQ<1), it was found that the investigated walnut genotypes were not risky for human health. © 2024, Hohere Bundeslehranstalt und Bundesamt fur Wein- und Obstbau Klosterneuburg. All rights reserved.
Schwermetallgehalt und Risikobewertung von Walnuss (Juglans regia L.), die im Aras-Becken in der Türkei angebaut wird.
Keywords: location; metal contamination; trace elements; Walnut